Social life standards and problems of poverty overcoming in Ukraine - Rojenko, Vita; Dobryk, Lilia (Skhid, 2013)
An outstanding role of the social policy and the necessity of their over thinking have been proved. The social standards in Ukraine have been characterized. According to Ukrainian legislative system social standards are the base of expenditures calculation on social purposes and formation of all level budgets on their base. Nowadays there is no system of social standards and guarantees in Ukraine. The formation of such a system requires the improvement of social legislation of the country